(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
The current study was conducted with the aim of knowing the changes in blood sugar in people with diabetes after giving a dose of general anesthesia for the purpose of performing surgical operations to the auditors of Imam Al-Sadiq Hospital (peace be upon him) and Al-Kifl General Hospital in Babel Governorate for the period from 3/1/2022 to 1/3/2022 by 30 samples ranging in age from (25-50) years 2 ml of venous blood was withdrawn and placed in a Gel tube, then placed in a centrifuge to separate the serum for the purpose of conducting a glucose test. The results showed that the diabetes test is 100% positive for diabetic patients. The results also showed a significant increase (P <0.05) in the blood sugar level after the operation compared to the blood sugar before the operation. We conclude from this study that general anesthesia has a moderate effect on diabetic patients after conducting a blood sugar test before and after the operation. >